Engendering Biopoetics of Testimony: Louise Dupré, Chus Pato, and Erín Moure - Quéma, Anne (Canadian Jewish Studies / Études juives canadiennes, 2021)
The act of bearing witness to the remnants of Auschwitz strains poetry and poetics. To examine manifestations of this disarray, this article first establishes a dialogue between philosophy and poetry by discussing Giorgio Agamben’s conception of testimony and Jacques Derrida’s reflection on the shibboleth. It goes on to consider writings by Louise Dupré, Chus Pato, and Erín Moure, who write as inheritors of necropolitical violence, yet at a remove from the Shoah. Although their writing practices cross paths with Agamben’s and Derrida’s reflections, these poets generate a biopoetics of testimony that exceeds these reflections by engendering a tension between dispossession and regeneration. L’acte de témoigner des vestiges d’Auschwitz met à mal la poésie et la poétique. Pour examiner les manifestations de ce désarroi, cet article établit d’abord un dialogue entre philosophie et poésie en abordant la conception du témoignage de Giorgio Agamben et la réflexion de Jacques Derrida sur le shibboleth. Il se penche ensuite sur les écrits de Louise Dupré, Chus Pato et Erín Moure, qui écrivent en héritiers de la violence nécropolitique, mais à distance de la Shoah. Bien que leurs pratiques d’écriture croisent les réflexions d’Agamben et de Derrida, ces poètes génèrent une biopoétique du témoignage qui dépasse ces réflexions en engendrant une tension entre dépossession et régénération.